Palladium-catalysed formation of vicinal all-carbon quaternary centres via propargylation - Xin Huang (Nature Portfolio, 2016)
Formation of vicinal, quaternary stereocentres is challenging, but such products are commonly encountered in nature. Here, the authors report a palladium catalysed process to form vicinal quaternary carbons via propargylation, including in enantiopure form when optically active starting materials are employed.